El control interno y su eficacia en la gestión de la Ferretería DON GALO del cantón Valencia provincia de Los Ríos año 2010 - Avecillas Muñoz, Cinthya Veronica (2012)
The Hardware store "Don Galo" is a company constituted legally, with about 7 years of experience on the market, located in the canton Valencia, of the province of The Rivers. Nowadays, the company there presents a lack of a system of internal control financial administrative officer who does not allow him to optimize his functions and to develop with efficiency the activities, in agreement to the recovered charges. For such a motive, there arose the need to design the necessary controls, to focus a specific vision of the goal to managing and extracting the whole profit to improve the administrative and financial management; establishing, policies, functions and procedures with his due controls and this way to improve day after day, for benefit of the consumers across the commercial innovative concept for this business type. The aim of the present work is to develop a based and documented offer, which allows them the persons in charge of the Hardware store "Don Galo", to know, to handle and to solve the administrative problems that they could present in the hardware store.